Efficiency of the Lausanne Clinical Pathway for Proximal Femoral Fractures - Fleury, Nicole; Chevalley, François; Rubli, Eve; Coti, Pauline; Farron, Alain; Jolles, Brigitte M. (Frontiers in Surgery, 2015)
Purpose/Introduction: The number of hip fractures is rising, due to increases in life expectancy. In such cases patients are at risk from post-operative complications and subsequently the average length of hospitalisation may be extended. In 2011, we established a clinical pathway (CP), a specific model of care for patient-care management, to improve the clinical and economic outcomes of proximal femoral fracture management in elderly patients. The goal was to evaluate the CP using clinical, process and financial indicators. Methods: We included all surgical patients aged 65 and over, admitted to the emergency department with a fracture of the proximal femur following a fall. Assessment parameters included three performance indicators: clinical, process and financial. The clinical indicators were the presence or absence of acute delirium on the third post-operative day, diagnosis of nosocomial pneumonia, and the number of patients fulfilling at least 75% of their nutritional requirements at the end of the hospitalisation period. The process indicator was the time interval between arrival at the emergency department and surgery. The financial indicator was based on the number of days spent in hospital. Results: From 2011 to 2013, 669 patients were included in the CP. We observed that the average length of stay in hospital decreased as soon as the CP was implemented and stabilised afterwards. The goal of 90% of patients undergoing surgery within 48 hours of arrival in the emergency department was surpassed in 2013 (93.1%). Furthermore, we observed an improvement in the clinical indicators. Conclusions: The application of a CP allowed an improvement in the qualitative and quantitative efficiency of proximal femoral fracture management in elderly patients, in terms of clinical, process and financial factors.